Association of Imposter Phenomenon and Burnout with Mode of Education among Medical Students of Pakistan - Farhat Ijaz; Uswah Bokhari; Sehar Khauteja Khan; Uswah Shoaib; Sana Tariq; Rana Zaid Haris; Rana Khurram Aftab (Aziz Fatimah Medical and Dental College, 2022)
Objective: Burnout and imposter phenomenon can significantly impact medical education. The aim of this study is to determine effect of imposter syndrome and burnout in medical students during online and face-face education in Pakistan.     Methodology: A cross-sectional study was conducted at CMH Lahore Medical College and Institute of Dentistry (CMH LMC & IOD) MBBS and BDS Department. Oldenburg Burnout Inventory was used for identifying burnout and Clance Impostor Phenomenon Scale was used for identifying imposter characteristics in students. All data collected online using Microsoft forms were given an identification number to maintain anonymity and confidentiality.  Results:The mean impostorism score was higher in face-to-face (in class education) education however, analysis of the Clance Impostor Phenomenon Scale (CIPS) showed no significant association of imposter characteristics with the mode of education with a p-value of 0.053. The mean score for total burnout was higher during online education. The difference in burnout, exhaustion and disengagement during online mode of education and face-to-face mode of teaching was significant with a p-value of 0.001, 0.001, 0.002 respectively.  Conclusions Imposter characteristics are an intrinsic factor not affected by external environment. However, burnout is higher during online education which can be overwhelming and should be taken into consideration when designing curricula. Key words: Imposter phenomenon, Burnout, Online Education, Traditional Education.